Quem tem boca vai comer na rua! Inovação social na comida de rua sobre rodas como prática em João Pessoa - PB - Almeida , Larissa Lucena (2017)
This research aimed to understand the process of social innovation of the practice of street food on wheels in the city of João Pessoa-PB. For this, the notion of practice and social innovation developed by Shove, Pantzar and Watson (2012) was used, who understand the practice as an entity or performance constituted of interdependent elements (competences, materials and meanings) that combined become order it and reproduce it, and social innovation as the process from which practice emerges, persists, changes and disappears, when the connections between these three types of element are made, sustained, or broken. As for nature, it is a qualitative research in which the approach to practices for access the field was used, also known as Practice-Based Studies (EBP) (NICOLINI; GHERARDI; YANOW, 2003). Based on this approach, the methods of shadowing (CZARNIWASKA, 2014) and the interview to the double (NICOLINI, 2009a) were used, which together made it possible to capture more reliable data in the field of study. Associated with the mentioned methods, the technique of zooming in and zooming out (NICOLINI, 2009b) was also used. The following instruments were used to collect the data: participant observation techniques, informal conversations, semi-structured interviews, photo and video analysis, and field diary. The unit of analysis considered in this study was street food on wheels as a practice. For the analysis of the data and consequent elaboration of the results, the interpretation was used in light of the approach of Shove, Pantzar and Watson (2012), who were inspired by the EBPs. The results indicate that there is strong evidence that street food on wheels is undergoing the process of social innovation, since the material elements, skills and meanings have changed and are still in the process of change, it is already possible to identify differences between practice traditionally developed and the "new" practice. The first change identified in the "new" practice was with regard to gourmetization, the second was the structure and layout of the vehicle used, the third was the form of communication, mainly through the use of social networks via smartphones, the fourth was the management form and the fifth the use of spaces. In addition, a new understanding about the practice of street food on wheels has emerged and is expanding because of the transformations that have occurred in the practice.